Effect of microwave sterilization and water storage on the Vickers hardness of acrylic resin denture teeth - Campanha, N. H.; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP]; Machado, Ana Lucia [UNESP] (Mosby, Inc, 2005)
Statement of problem. Acrylic resin denture teeth soften upon immersion in water, and the heating generated during microwave sterilization may enhance this process.Purpose. Six brands of acrylic resin denture teeth were investigated with respect to the effect of microwave sterilization and water immersion on Vickers hardness (VHN).Material and Methods. The acrylic resin denture teeth (Dentron [D], Vipi Dent Plus [V], Postaris [P], Biolux [B], Trilux [T], and Artiplus [A]) were embedded in heat-polymerized acrylic resin within polyvinylchloride tubes. For each brand, the occlusal surfaces of 32 identical acrylic resin denture posterior teeth were ground flat with 1500-grit silicon carbide paper and polished on a wet polishing wheel with a slurry of tin oxide. Hardness tests were performed after polishing (control group, C) after polishing followed by 2 cycles of microwave sterilization at 650 W for 6 minutes (MwS group), after polishing followed by 90-day immersion in water (90-day Wim group), and after polishing followed by 90-day storage in water and 2 cycles of microwave sterilization (90-day Wim + MwS group). For each specimen, 8 hardness measurements were made and the mean was calculated. Data were analyzed with a 2-way analysis of variance followed by the Bonferroni procedure to determine any significance between pairs of mean values (alpha=.01).Results: Mircrowave sterilization of specimens significantly decreased (P <.001) the hardness of the acrylic resin denture tooth specimens P (17.8 to 16.6 VHN, V (18.3 to 15.8 VHN), T (17.4 to 15.3 VHN), B (16.8 to 15.7 VHN), and A (17.3 to 15.7 VHN). For all acrylic resin denture teeth, no significant differences in hardness were found between the groups Mws, 90-day Wim, and 90-day Wim + MwS, with the exception of the 90-day Wim + MwS tooth A specimens (14.4 VHN), which demonstrated significant lower mean values (P <.001) than the 90-day Wim (15.8 VHN) and MwS (15.7 VHN) specimens.Conclusions. For specimens immersed in water for 90 days, 2 cycles of microwave sterilization had no effect on the hardness of most of the acrylic resin denture teeth.